Оптимізація освітлення в Unreal Engine 5 - Борисенко, А. Е. (ХНУРЕ, 2024)
This work explores the application of Virtual Shadow Maps (VSM) and Lumen Global Illumination and Reflections (Lumen GI) to improve the visual quality and realism of virtual environments in Unreal Engine 5. The work describes how to improve the level of detail and lighting in a game environment in Unreal Engine 5. It also provides a visual comparison of Virtual Shadow Maps (VSM) and Shadow Mapping in Unreal Engine 5. The reproduction of clear, realistic shadows using Virtual Shadow Maps (VSM) and Lumen Global Illumination and Reflections (Lumen GI) is demonstrated.
Keywords: Unreal Engine 5; освітлення